Differences in crystallization of two LinB variants from Sphingobium japonicum UT26 - Degtjarik, Oksana (International Union of Crystallography, 2013)
Haloalkane dehalogenases are microbial enzymes that convert a broad range of halogenated aliphatic compounds to their corresponding alcohols by the hydrolytic mechanism. These enzymes play an important role in the biodegradation of various environmental pollutants. Haloalkane dehalogenase LinB isolated from a soil bacterium Sphingobium japonicum UT26 has a relatively broad substrate specificity and can be applied in bioremediation and biosensing of environmental pollutants. The LinB variants presented here, LinB32 and LinB70, were constructed with the goal of studying the effect of mutations on enzyme functionality. In the case of LinB32 (L117W), the introduced mutation leads to blocking of the main tunnel connecting the deeply buried active site with the surrounding solvent. The other variant, LinB70 (L44I, H107Q), has the second halide-binding site in a position analogous to that in the related haloalkane dehalogenase DbeA from Bradyrhizobium elkanii USDA94. Both LinB variants were successfully crystallized and full data sets were collected for native enzymes as well as their complexes with the substrates 1,2-dibromoethane (LinB32) and 1-bromobutane (LinB70) to resolutions ranging from 1.6 to 2.8 Å. The two mutants crystallize differently from each other, which suggests that the mutations, although deep inside the molecule, can still affect the protein crystallizability.